(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2015)
An accurate biostratigraphic study of the Paleocene-middle Eocene calcareous nannofossils was performed on the turbiditic successions that characterize the Northern Apennines Mt. Caio, Farini d’Olmo, Mt. Sporno and Mt. Penice Units, belonging to the “Tertiary Flysch Auctt.” and referable to the External Ligurides. This geologic complex accumulated in a link key area, located between the oceanic Ligure-Piedmontese domain and the Adria continental margin. The reference biostratigraphic scheme used in the study is the recently published calcareous nannofossil biozonation proposed for the Paleogene by Agnini et al. (2014). The obtained biostratigraphic and chronostratigraphic data suggest that further investigation is needed to clarify the tectono-sedimentary evolution and to unravel the complex architecture of the External Ligurides.